2008
DOI: 10.1016/j.febslet.2008.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional secretion of fibroblast growth factor 2 and galectin‐1 does not require shedding of plasma membrane‐derived vesicles

Abstract: Various molecular mechanisms of unconventional secretion of fibroblast growth factor 2 and galectin-1 have been proposed. A non-vesicular pathway that is based on direct translocation across the plasma membrane has been described. In other studies, however, release into the extracellular space of cell-derived vesicles was implicated in both FGF-2 and Gal-1 secretion. Such vesicles were proposed to originate either from plasma membrane shedding or by the release of exosomes. Employing an inhibitor of plasma mem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 39 publications
0
46
0
1
Order By: Relevance
“…Altogether, these data suggest that tumor cells can secrete galectin-1 to promote tumor progression. Interestingly, galectin-1 is secreted by a nonclassic pathway, and there seem to exist common features between the secretion of galectin-1 and that of bFGF, another potent proangiogenesis growth factor (30)(31)(32). Moreover, Le and colleagues found a correlation between the expression of galectin-1 and the hypoxia marker CA-IX (33,34).…”
Section: Discussionmentioning
confidence: 97%
“…Altogether, these data suggest that tumor cells can secrete galectin-1 to promote tumor progression. Interestingly, galectin-1 is secreted by a nonclassic pathway, and there seem to exist common features between the secretion of galectin-1 and that of bFGF, another potent proangiogenesis growth factor (30)(31)(32). Moreover, Le and colleagues found a correlation between the expression of galectin-1 and the hypoxia marker CA-IX (33,34).…”
Section: Discussionmentioning
confidence: 97%
“…1C). To our knowledge, this is the first report of Lefty proteins using an exosomal pathway for extracellular release, and it extends the growing list of proteins/ growth factors employing this transport route [30][31][32][33]. Undoubtedly, proteins marked for exosomal delivery constitute part of an elaborated ''exsosomal code'' unique to the cells of their origin, which is thus far incompletely deciphered.…”
Section: Lefty Is Secreted Through An Exosomal Pathwaymentioning
confidence: 99%
“…3D). In contrast, experiments by other groups using non-differentiated cells, such as CHO and HeLa, have suggested that secretion of galectins is independent of microvesicles (53,54). Interestingly, upon recognition of β -glucan, the major component of fungal cell walls, by the C-type lectin, dectin-1, macrophages secrete galectin-3 in a manner dependent on inflammasome activity and an active autophagic process, indicating release through the autophagic pathway ( …”
Section: B Release Of Galectins Into Extracellular Spacementioning
confidence: 63%